Nonconvulsive status epilepticus during childhood: clinical and electroencephalographic features - (:unkn) unknown (TURKISH J PEDIATRICS, 2008)
Data from eight patients, ranging from 2.8-15 years old (median 8.7 years), treated with the diagnosis of NCSE were evaluated on clinical basis. The patients attended the hospital with acute confusional state ranging from sudden onset of verbal cooperation insufficiency to aimless-meaningless behavior and confusion without any motor component of seizure. While five of the cases were diagnosed and followed up with epilepsy, the other three had no history of epilepsy. No reason was detected that could cause acute encephalopathy. EEG examinations during acute confusional state showed partial or generalized continuous electrographic seizure activity lasting at least 30 minutes without clinical seizure activity. After administration of intravenous antiepileptic medication, the confusional states of the patients recovered, and the EEG examinations showed normal baseline activity with significantly diminished discharges or complete normal waveform. Nonconvulsive status epilepticus should be considered in all children admitted to the hospital with acute unexplained encephalopathy, whether they have a history of epilepsy or not. Emergent EEG examination should be a routine part of evaluation in these children for the diagnosis and treatment of NCSE.
Keywords: nonconvulsive status epilepticus; childhood; REFRACTORY STATUS EPILEPTICUS; EEG; TRANSIENT; SEIZURES